Potential synergistic effect of polystyrene nanoplastics on cadmium toxicity to Sedum alfredii Hance - Yuenan Li; Hongyan Cheng; Yixiu Wang; Yonghui Lv; Ruiyan Ning; Haibo Zhang; Qing Wang; Na Liu (PLoS ONE, 2026)
Micro/nanoplastics (MPs/NPs) and cadmium (Cd) are among the most serious pollutants in soils, and the coexistence of MPs/NPs and Cd is therefore inevitable. Several studies have investigated the effects of MPs/NPs or Cd stress alone on plant growth. However, little is known regarding the combined effects of NPs and Cd stress on plants and Cd accumulation, particularly in hyperaccumulators. The study selected Sedum alfredii Hance as a test material, and investigated the individual and combined effects of polystyrene nanoplastics (PS-NPs) (100 and 1000 mg·kg -1 ) and Cd (0.6 and 4 mg·kg -1 ) on the physiological indices, trace element contents, Cd content, Cd chelation, and Cd speciation. The growth of S. alfredii was significantly inhibited under PS-NPs or Cd alone, and the inhibitory effect of Cd stress was more significant than that of PS-NPs stress. Combined treatments increased the growth-inhibition effect. The individual PS-NPs treatments had no significant effects on antioxidant enzyme activity or malondialdehyde (MDA) and trace element contents, but combined treatments significantly increased antioxidant enzyme activity and MDA content, thereby reducing the trace element contents compared to the individual PS-NPs or Cd treatments. Combined treatments increased the contents of the exchangeable Cd, carbonate-bound Cd, and reduced organic-bound Cd, thereby significantly increasing the Cd content in the aboveground parts and roots of S. alfredii ; the Cd content in the aboveground parts and roots of S. alfredii under combined Cd (4 mg·kg -1 ) and PS-NPs (1000 mg·kg -1 ) treatment was 1.2-fold and 1.36-fold higher, respectively, than under Cd stress alone (4 mg·kg -1 ). Furthermore, Cd chelation under combined treatments increased significantly compared to the PS-NPs or Cd treatments alone. The nonprotein thiol (NPT) and phytochelatin (PC) contents under combined PS-NPs (1000 mg·kg -1 ) and Cd (4 mg·kg -1 ) increased by 12.9% and 13.0%, respectively, compared to Cd stress alone (4 mg·kg -1 ). These findings elucidate the impact of NPs on Cd accumulation in hyperaccumulator plants, which holds significant implications for understanding the environmental risks associated with the combination of NPs and Cd.